THE EFFECT OF GLOBAL PANDEMIC COVID-19 AND ECONOMIC INDICATORS ON FTSE BURSA MALAYSIA KLCI STOCK RETURNS VOLATILITY: AN EXPLORATORY SEQUENTIAL MIXED METHODS APPROACH (Journal of International Studies, 2025)
Malaysia’s stock markets experienced significant declines as the virus spread throughout the global pandemic of COVID-19. This study was undertaken to investigate the global pandemic COVID-19 and Malaysia stock market volatility during the Movement Control Order from 18 March 2020 until 30 September 2022 using a mixed method of quantitative and qualitative data. The Exponential Generalized Autoregressive Conditional Heteroskedastic (EGARCH) methodology was employed to analyse identified quantitative variables and understand stock return patterns, along with a qualitative exploratory sequential mixed methods approach to investigate the phenomenon. The EGARCH empirical finding reveals statistically positive coefficients and highlights substantial continuity in Malaysia’s stock market return volatility, besides negative shocks and significance between the variables in considering uneven volatility and their impact on FTSE Bursa Malaysia KLCI stock returns, except for Malaysia’s gold price.